FISIOLOGIA REPRODUTIVA EM ÉGUAS – BREVE REVISÃO - da Silva, Tais Lopes; Batiston, Nicoli; Alves, Bruna Farias; Travi, Magdalena Reschke Lajús; Carneiro, Maico Fernando Wilges; Danelus, Marina Oliveira (Anais de Medicina Veterinária, 2022)
.